Impact of Ni content on the thermoelectric properties of half-Heusler TiNiSn. Issue 2 (22nd January 2018) - Tang, Yinglu; Li, Xiaoshuang; Martin, Lukas H. J.; Cuervo Reyes, Eduardo; Ivas, Toni; Leinenbach, Christian; Anand, Shashwat; Peters, Matthew; Snyder, G. Jeffrey; Battaglia, Corsin
Abstract : Thermoelectric properties vary dramatically between two boundary compositions of Ni-rich and Ni-poor TiNiSn, up to 25% in zT . Abstract : From phase boundary mapping, we find that the thermoelectric TiNiSn half-Heusler phase shows a narrow solubility range on the Ti–Ni–Sn phase diagram primarily in the range of excess Ni that can be approximated as TiNi1+ x Sn, where x is temperature dependent with 0 ≤ x ≤ 0.06 at 1223 K. Four phase boundary compositions with different Ni contents associated with four three-phase regions are identified. We characterize the thermoelectric properties of these stable compositions and find significant difference between Ni-rich and Ni-poor phase boundary compositions of TiNiSn, which amounts up to 41%, 58%, and 25% difference in the Seebeck coefficient, lattice thermal conductivity, and thermoelectric figure of merit respectively. This explains the large discrepancy of literature data on the thermoelectric properties of TiNiSn within a unified phase diagram framework. We demonstrate that Ni-rich TiNiSn results in a narrower band gap using the Goldsmid formula, which we interpret to be due to the formation of an impurity band from interstitial Ni in the forbidden gap as previously suggested. Interstitial Ni atoms scatter both electrons and phonons, with the latter effect being much stronger, thus a lower lattice thermal conductivity compensates for the decrease in electron mobility leading to a high zT value of 0.6 at 850 K for intrinsic Ni-rich TiNiSn. With Sb doping, the carrier concentration in these stable boundary compositions can be tuned but the distinct features in their transport properties remain unchanged. A maximum zT value of 0.6 was also achieved at 850 K for intrinsic Ni-poor TiNiSn upon Sb doping.